Rapid synthesis: Determining the features of managed alcohol programs - Mattison, CA; Belesiotis, P; Wilson, MG (My University, 2019)
An assessment of what is known about features of managed alcohol programs. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum’s Rapid Response program.
Keywords: alcohol programs